Therapist-led and self-led one-session virtual reality exposure therapy for public speaking anxiety with consumer hardware and software: A randomized controlled trial. (January 2019) - Lindner, Philip; Miloff, Alexander; Fagernäs, Simon; Andersen, Joel; Sigeman, Martin; Andersson, Gerhard; Furmark, Tomas; Carlbring, Per
Highlights: Therapist-led Virtual Reality (VR) exposure therapy reduced public speaking anxiety. Internet-administered, self-led VR exposure therapy reduced public speaking anxiety. Results were maintained or improved at six and twelve month follow-ups. Abstract: Public speaking anxiety (PSA) is a common condition which can be treated effectively with exposure therapy. However, inherent difficulties in stimuli presentation and control limits dissemination and the therapeutic potential. Virtual Reality (VR) technology has the potential to resolve these issues and provide a scalable platform for self-help interventions. No previous study has examined whether this can be achieved using the first generation of consumer VR hardware and software. In the current trial, n = 25 + 25 participants were randomized to either one-session therapist-led VR exposure therapy for PSA followed by a four-week internet-administered VR to in-vivo transition program, or a waiting-list. Linear mixed effects modeling revealed significant, large (within Cohen's d = 1.67) decreases in self-reported PSA. The waiting-list was then given access to an internet-administered, self-led version of the same VR exposure therapy to be conducted at home, followed by the same transition program. Dual-slope mixed effects modeling revealed significant, large (d = 1.35) decreases in self-reported PSA. Results were maintained or improved at six- and twelve-month follow-ups. We show for the first time that low-cost, off-the-shelf consumer VR hardware and software can be used to conduct exposure therapy for PSA, both in the traditional, previously impractical one-session format, and in a novel self-led, at-home format.